Leaf tissue replacement in Brachiaria humidicola CIAT 6133 with different defoliation management - Martínez Méndez, Daniel; Enríquez Quiroz, Javier Francisco; Esqueda Esquivel, Valentín Alberto; Ortega Jimenez, Eusebio (Revista Mexicana de Ciencias Agrícolas, 2020)
The defoliation in the tissue replacement of Brachiaria humidicola CIAT 6133 was evaluated by cuts at 9, 12 and 15 cm in height, harvested at 3, 4 and 5 and 5, 6 and 7 weeks in rains and norths, respectively. Every seven days the leaf appearance rate (LAR), leaf elongation rate (FER), leaf senescence rate (LSR) and net leaf growth (NFG) and stem density (DS) were measured every month. In rains, the highest LAR was 0.097 leaves stem-1 day-1 with cuts at 15 cm, every three weeks, in north 0.044 leaves stem-1 day-1 with cuts at 9 cm and 0.047 leaves stem-1 day-1 every seven weeks. The highest FER and NFG occurred with cuts at 15 cm; in rains of 1.85 and 1.81, and in norths of 0.53 and 0.45 cm stem-1 day-1, respectively. In rains the highest FER occurred in week two of the regrowth (1.8 cm stem-1 day-1), while in the north it was in week three of regrowth (0.45, 0.5 and 0.46 cm stem-1 day-1). The LSR increased from week four onwards in both seasons. The DS was maximum at three and four weeks in rains and norths, at five and six weeks. The greatest leaf growth occurred in sections 15 cm high three weeks after regrowth, regardless of the interval between cuts and time of year, and the highest stem density at three and four weeks in rains and five and six weeks in norths.
Keywords: Brachiaria humidicola CIAT 6133 cv. Isleño; defoliation management; leaf tissue replacement